Child Education in the Perspective of the Qur’an: Strategies For Shaping A Morally Upright Generation - Qoyimah, Durotul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to examine the concept of child education from the perspective of the Qur’an, using it as a foundation for Islamic values from an early age. As a guide for Muslims, the Qur’an contains various instructions related to parenting and child development, both morally, spiritually, and socially. This research focuses on several relevant verses of the Qur’an, including Surah Luqman: 13–19, At-Tahrim: 6, An-Nur: 58, Al-Ahqaf: 15, and Al-Isra: 23–24, to explore the educational values embedded within them. The study employs a qualitative approach using a library research method. Data were obtained through document analysis and a review of relevant scholarly literature. The data analysis technique used is content analysis, aimed at interpreting the meaning of the verses in a systematic and in-depth manner. The validity of the data is ensured through source triangulation to maintain objectivity and scholarly depth. The findings indicate that the Qur’an places great emphasis on child education, encompassing aspects of monotheism (tawhid), morality (akhlaq), parental responsibility, and early moral habituation as the foundation for an Islamic way of life.